2000
DOI: 10.1051/agro:2000111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and characterisation of a collection of wild Spanish populations of the genera Elymus and Thinopyrum using morphological and agronomical traits

Abstract: International audienceQuantification of the variability in wild species is a necessary step before determining their possible future use in plant breeding. A collection of 29 wild Spanish populations of the genera Elymus and Thinopyrum was characterised using 22 morphological and agronomical characteristics. Field studies were performed over two years, 1994 and 1995. Frequencies were calculated for qualitative and quantitative traits. Pearson's product-moment correlation coefficient was used to analyse inter-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Interpopulational variability was also high and specimens with identical phenotypes were not found in different populations. In a separate study, the analysis of these populations according to morphological characters indicated a high degree of intra‐and interpopulational variation (N ieto ‐L ópez et al 2000).…”
Section: Discussionmentioning
confidence: 91%
“…Interpopulational variability was also high and specimens with identical phenotypes were not found in different populations. In a separate study, the analysis of these populations according to morphological characters indicated a high degree of intra‐and interpopulational variation (N ieto ‐L ópez et al 2000).…”
Section: Discussionmentioning
confidence: 91%